Pengaruh Financial Literacy, Risk Tolerance, Financial Attitude, dan Investment Experience terhadap Keputusan Investasi : (Studi pada Karyawan Milenial BRI Tower Jakarta) - Muhammad Mifdhol Rahman; Retno Fuji Oktaviani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Investment decision-making among millennials in Indonesia is not only influenced by rational considerations but also by behavioral and psychological factors, which can be explained using the Theory of Planned Behavior (TPB). Millennials represent the most active group in adopting digital financial services and participating in various capital market instruments, making it important to understand the determinants of their investment behavior. This study aims to analyze the influence of financial literacy, risk tolerance, financial attitude, and investment experience on investment decisions among millennial employees. The research employed a quantitative design by distributing structured questionnaires to 100 respondents selected using an incidental sampling technique. The study population consisted of millennial employees working at BRI Tower 2, Jakarta. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach, processed through SmartPLS version 4.1.1.2. The results indicate that financial literacy, risk tolerance, and financial attitude significantly and positively affect investment decisions, whereas investment experience has a positive but insignificant effect. These findings confirm the TPB framework, in which financial literacy and financial attitude strengthen attitude toward behavior, while risk tolerance reflects perceived behavioral control. However, investment experience alone is not sufficient to consistently shape rational decision-making. This research contributes theoretically to behavioral finance studies and extends the application of TPB in the context of investment behavior. Practically, the findings imply the need for organizations and policymakers to design targeted financial literacy programs and initiatives that foster positive financial attitudes. Strengthening these aspects is expected to encourage sustainable and rational investment practices among young employees in Indonesia.